2017
DOI: 10.1021/acsami.6b16412
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Omnidirectional Light Trapping in Gold-Decorated ZnO Nanopillar Arrays

Abstract: The photoluminescence (PL) and reflectivity characteristics of zinc oxide nanopillars (ZnO-NPs) grown on indium-tin-oxide (ITO)-coated glasses were investigated. The room temperature PL showed bright white-light emission for the undoped ZnO-NPs grown at 600 °C, suggesting the close relation between the optical characteristic and the growth conditions being carried out for obtaining the present ZnO-NPs. The reflectivity of the as-grown ZnO-NPs array was about ∼29% with the wavelength of the incident light rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Synthesis of metal-based nanocomposites by organic solvent-free conditions has drawn a lot of attention in the current decade (Li et al, 2013;Yao et al, 2013;Zhang et al, 2016;Qi et al, 2019;Ritchie et al, 2019). Au-ZnO nanocomposites, which are well known for a variety of applications, have been synthesized at high temperature in the presence of organic solvent (Yao et al, 2011;Tahir et al, 2013;Hang et al, 2016;Chang et al, 2017;Lupan et al, 2019). There are two reports, where AuNP was decorated on the crystalline ZnO nanorod surface at high temperature (Unlu et al, 2015;Ning et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of metal-based nanocomposites by organic solvent-free conditions has drawn a lot of attention in the current decade (Li et al, 2013;Yao et al, 2013;Zhang et al, 2016;Qi et al, 2019;Ritchie et al, 2019). Au-ZnO nanocomposites, which are well known for a variety of applications, have been synthesized at high temperature in the presence of organic solvent (Yao et al, 2011;Tahir et al, 2013;Hang et al, 2016;Chang et al, 2017;Lupan et al, 2019). There are two reports, where AuNP was decorated on the crystalline ZnO nanorod surface at high temperature (Unlu et al, 2015;Ning et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For the last two decades, ZnO nanostructures have garnered substantial attention because of their prodigious potential for blue and ultra-violet (UV) optoelectronic devices [1][2][3][4][5][6]. Among various nanostructures, 1-dimensional ZnO (e.g., nanorod [7,8], nanoneedle [9,10], nanopillar [11,12], etc.) is one of the most attractive nanoarchitectures due to its short pathway for carrier transport [13], high surface-to-volume ratio for photon collection [14], and low exciton-phonon coupling strength [15].…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al have found that based on the composite of ZnO nanorods and TiO 2 , the band edge emission of ZnO nanorods can be enhanced up to 120 times . For optoelectronic devices, doped ZnO films have also been deposited . The properties of the ZnO–TiO 2 system that are responsible for the luminescence performance therefore becomes an interesting issue.…”
Section: Introductionmentioning
confidence: 99%